Influence of dietary olive paste flour on the performance and oxidative stress in chickens raised in field conditions - FOTOU, E; MOULASIOTI, V; ANGELIS, I; TSIOURIS, V; PATSIAS, A; TELLIS, C; MOUSSIS, V; BOTI, ME; TSOUKATOS, D (Journal of the Hellenic Veterinary Medical Society, 2021)
Olive oil contains a variety of antioxidants, including vitamin E. Its consumption protects against oxidative stress, which is involved in many pathological conditions, affecting animals’ development and their general welfare. The present study aimed to investigate the effect of olive paste flour (OPF) on the antioxidant status and performance of broiler chickens raised in field conditions. Total of 18.000 broilers was randomly allocated in equal numbers in two poultry houses. The chickens were grouped according to their diet as follows: Control group: chickens fed commercial poultry feed, and OPF group: chickens fed control dietsin the starter period, but they got a supplement of OPF in grower, and finisher 1 and 2periods, respectively. The birds were raised under identical field conditions (ventilation, vaccination, lighting, etc.). Antioxidant status was assessed by measuring the concentration of vitamin E in plasma, as well as the total antioxidant capacity (TAC) in plasma and muscle tissue. According to the statistical analysis of the results, the addition of OPF to chickens’ diet significantly enhanced plasma α-tocopherol concentration (p≤0.05). TAC did not show any significant differences in chicken plasma nor muscle tissue(p>0.05).Feed intake (FI) was higher in OPF group, while Body weight (BW) was lower. Liveability was similar for the two groups. The feed conversion ratio (FCR) was higher, and the European production efficiency factor (EPEF) was lower in broilers of the OPF group compared to those of the control group.Samples of roasted breast from chickens of both groups were used for organoleptic characteristics evaluation. Results showed that samples of the OPF group smelled more intensely and were more tasteful than those of the control group.However, other organoleptic characteristics did not differ. In conclusion, the results demonstrated that although the addition of OPF to chickens’ diet can cause growth retardation, it can significantly increase the plasma α-tocopherol concentration. Further studies are needed to optimize the concentration of OPF in poultry feed in order to avoid growth retardation or even to promote growth in broiler chicks.